Discourse personalization: weblog's potential to transform the public sphere - Requejo Alemán, José Luis (2008)
Born in the last decade of 20th century, weblogs have turned into a phenomenon that comes out of what, until now we ha ve known as wide, heterogeneous and disperse borders of mass communication. Supported on RSS formar {Really Simple Sindication, XML's dialect), weblogs are changing the way users make use of the Internet. In fact, the web was only a source of information and now is a space of communicative feedback. This is sealing rhe rransformation of public sphere from rraditional ro pointcasring. The resulr for journalist would mean having rheir broadcasting usefulness limited ro traditional media. The aim of this paper is to analyze the weblog transformation potencial in the public sphere by observing the changes inflicted on publishing traditional process. Ir constituted of rhree epigraphs: first, one analyzes historical-technical characteristics ofweblogs's feedback rewarded with recognized award Bloggin 2004; second, an introduction to essenrial characteristics of public sphere according to Víctor Sampedro (2000) and José Luis Dader (1992); and third, one outlines a projection on what ir might be its fu tu re with one incubarion analyzes of messagescontained in first pages of weblogs winners 2004